THYROID PATHOLOGY AND IODINE SUPPLY CONDITION IN THE POLTAVA REGION IN 20 YEARS AFTER CHERNOBYL DISASTER - Bobyrova, L.E.; Gorodinskaya, O.Y. (World of Medicine and Biology, 2014)
The article analyzes data on the prevalence of thyroid pathology in Ukraine and Poltava region for 20 years after the Chernobyl disaster. The study of iodine, fluorine and radionuclides containing in drinking water, what Poltava region residents use, was held. This study allowed to establish the following: the trigger for thyroid pathology development in general in Poltava region is moderate reduction of iodine in the environment. Also the imbalance between iodine and fluorine as well as the radionuclide contamination, determine thyroid disease structure in this particular region. On this bases, the development of new methods in prevention and treatment of endemic goiter should be hold, considering the environmental conditions of the region.